A necessary and sufficient single‐profile condition for transitivity of the Pareto extension order. (December 2013) - Xefteris, Dimitrios
<x xml:space="preserve">Abstract</x> This note identifies a necessary and sufficient single‐profile condition for transitivity of the Pareto extension order when individuals are never indifferent between two distinct alternatives. We find that the Pareto extension order is transitive if and only if for any triplet of the available alternatives there exists either a consensus on which is the best, the second best or the worst alternative, or a perfect disagreement on which is the best or the worst alternative.